Water Temperature at Different Depths Affects the Distribution of Neon Flying Squid (Ommastrephes bartramii) in the Northwest Pacific Ocean - Wang, Jintao; Cheng, Yiqi; Lu, Huajie; Chen, Xinjun; Lin, Lei; Zhang, Junbo (Frontiers in Marine Science, 2022)
Ommastrephes bartramii can vertically swim during its life and previous studies have suggested the need to account for preferred habitat distribution influenced by water temperatures at different depths. To explore impacts of deep-water temperature on O. bartramii spatial distribution, we constructed generalized additive models (GAM) based on Chinese squid-jigging fishery data and the Argo deep water temperature data during 2005-2018 in the Northwest Pacific Ocean to analysis the relationships between the local abundance of O. bartramii and deep-water temperatures. The results showed that the variables including surface water temperature (T0), water temperature at 30-meter and 100-meter depths (T30, T100), and water differences between T0 and T30 (D0-30) significantly affected the O. bartramii spatial distribution. The suitable ranges of each variable are different, > 15.5 °C for T0, 11 – 18 °C for T30, < 6 °C for T100 and 4 – 4.5 °C for D0-30. The areas occupied by the suitable T30 seemed to reflect the outline of fishing ground, whereas the areas with suitable T100 were to indicate the high density of O. bartramii. The predicted suitable habitat area and high-density area for O. bartramii also regulated by ENSO events. We demonstrate how estimates of O. bartramii spatial distribution would vary influenced by deep-water temperatures in the Northwest Pacific Ocean. This information may help develop appropriate method for investigating effects of deep-water temperature on species with vertical migration.